An unusual case of diffuse pigmented villonodular synovitis of the shoulder: A multidisciplinary approach with arthroscopic synovectomy and adjuvant radiotherapy - Serra, Tânia Quinás (Eur J Rheumatol, 2017)
Pigmented villonodular synovitis (PVNS) is a rare proliferative disorder of the synovial membrane. This condition is usually monoarticular, can be locally destructive, and involves muscles, tendons, bursae, bones, and skin. The most commonly affected joints are the knee and hip, followed by the ankle and shoulder. Patients often present with pain, swelling, and joint effusion; however, the duration of symptoms varies. Total synovectomy is the preferred treatment for PVNS. Subtotal synovectomy is a factor of recurrence, and in diffuse PVNS, total excision is very difficult to achieve. Radiotherapy may have an adjunctive role, particularly in incomplete resection or as a treatment of salvation in recurrent cases. This treatment modality has low toxicity levels and enables satisfactory joint function. This is a case report of a rare case of diffuse PVNS of the shoulder that was treated with partial arthroscopic synovectomy and adjuvant radiotherapy. A 74-year-old male patient presented with gradual onset pain, hemarthrosis, and functional impairment of the right shoulder without previous trauma history. Magnetic resonance imaging of the shoulder demonstrated a diffuse synovial thickening that was compatible with PVNS and rotator cuff destruction. The lesion was partially excised by arthroscopy. The patient underwent adjuvant radiation therapy with a total dose of 40 Gy/20 fractions/4 weeks. At the final follow-up, i.e., 1 month after treatment, the patient had increased shoulder mobility and no pain, with a mild change in cutaneous pigmentation. Radiation therapy is safe and effective in treating and preventing recurrence of diffuse PVNS, particularly after incomplete synovectomy.